2012
DOI: 10.1590/s1415-43662012000700015
|View full text |Cite
|
Sign up to set email alerts
|

Deposição de gotas no dossel e controle químico de Phakopsora pachyrhizi na soja

Abstract: R ESU M OA deposição de gotas no dossel da cultura da soja com três pontas de pulverização e programas de controle químico da ferrugem asiática foram avaliados em experimento conduzido em campo, no município de Itaara, RS. Os tratamentos foram arranjados no delineamento de blocos ao acaso com quatro repetições, em esquema fatorial 2 x 3 x 3, representados por duas cultivares de soja, três pontas de pulverização e três programas de controle da ferrugem asiática. Os fungicidas foram aplicados nos estádios R1 e R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
1
26
0
4
Order By: Relevance
“…It must be observed that plant architecture has a direct influence on the efficiency of the application technology of agrochemicals. Tormen et al (2012) verified that soybean cultivars with higher LAI and more lateral ramifications close the canopy faster and make the penetration of the water droplets into the bottom of the plant difficult. Ozkan et al (2007) also verified that with a LAI of 6.4 most droplets are retained in the upper canopy, facilitating the proliferation of diseases in the lower canopies, which are chemically unprotected and have a favorable microclimate.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…It must be observed that plant architecture has a direct influence on the efficiency of the application technology of agrochemicals. Tormen et al (2012) verified that soybean cultivars with higher LAI and more lateral ramifications close the canopy faster and make the penetration of the water droplets into the bottom of the plant difficult. Ozkan et al (2007) also verified that with a LAI of 6.4 most droplets are retained in the upper canopy, facilitating the proliferation of diseases in the lower canopies, which are chemically unprotected and have a favorable microclimate.…”
Section: Introductionmentioning
confidence: 82%
“…According to Tormen et al (2012), the leaves of the plant top intercept a considerable part of the sprayed droplets, preventing the lower leaves from receiving significant amounts of active ingredient in the plant health control. Therefore, the plant lower part is highly dependent on the plant architecture, as well as leaf area and LAI.…”
Section: Figmentioning
confidence: 99%
“…When analyzing the effect of the air supply through a series of works, Oliveira et al (2016) indicated that this mechanism of support to the spray bar had no effect on the performance of agrochemicals and the control levels of phytopathogenic fungi. The contrasting and variable effects on the Vortex ® system may be associated with the different canopy opening levels, which can be influenced by the plant arrangement (Holtz et al, 2014), depending on the characteristic of the cultivar Tormen et al, 2012), as well as by the time of the day of spraying, due to the variation of the horizontal angle of soybean leaves throughout the day (Graziano et al, 2017;Moura et al, 2017). Moreover, the spray tip angle, droplet size and speed, adjuvants and mixture volume are factors that also influence droplets' penetration along the canopy of the plant (Cunha et al, 2014, Madureira et al, 2015Prado et al, 2015;Cunha et al, 2016;Weber et al, 2017, França et al, 2018.…”
Section: Resultsmentioning
confidence: 99%
“…In the application of systemic fungicide, the pulverized spray solution must remain in contact with the leaf for a minimum period, so that the plant can absorb the active ingredient, according to Yu et al (2009). In this sense, the active ingredient needs to be placed in the target under the risk of not controlling the disease (Tormen et al, 2012). Therefore, it is possible to emphasize that the spray nozzles that contributed to the lower AUDPC of the soybean rust and for greater safety in the application in relation to the other spray nozzles used were the Hypro GUARDIAN 120015 single pre-orifice flat spray, showing medium drop characteristics.…”
Section: Resultsmentioning
confidence: 99%